Not all uncertainty is treated equally: Information search under social and nonsocial uncertainty. (2nd June 2021) - Fleischhut, Nadine; Artinger, Florian M.; Olschewski, Sebastian; Hertwig, Ralph
Abstract: The social world is often portrayed as being less predictable and more uncertain than the nonsocial world. People may therefore feel the need to search more for information before making a choice. However, we suggest that cognitive tools such as social projection and norm‐based expectation may help people to predict others' behaviors in the social world and thus serve as a substitute for information search. We argue that in situations where the environment affords this possibility, social uncertainty may in fact trigger less search than nonsocial uncertainty. Consistent with our expectations, findings from two experiments showed that participants sampled considerably less and systematically differently in a mini‐ultimatum game (mUG; social uncertainty) than in structurally identical lotteries (nonsocial uncertainty). Even selfish individuals sensitive to the risk of rejection did not sample more than others, let alone as much as people in lotteries. Raising the stakes strongly increased sampling effort in lotteries but not in the social game. When evaluating risks based on outcomes alone, participants also anticipated searching less in mUGs than in lotteries, indicating that they were aware of norm‐based regularities in social worlds and that they exploited those regularities to guide their expectations. The findings highlight that the structure of social environments can enable decision makers to use cognitive tools to navigate uncertainty without needing to invest in extensive search.